Allometric relationship between body mass and aerobic metabolism in zebrafish Danio rerio. Issue 4 (13th March 2014) - Lucas, J.; Schouman, A.; Lyphout, L.; Cousin, X.; Lefrancois, C.
<x xml:space="preserve">Abstract</x> The relationship between body mass (M) and metabolic rate was investigated through the assessment of active (RA) and standard (RS) metabolic rate at different life stages in zebrafish Danio rerio (5 day‐old larvae, 2 month‐old juveniles and 6 month‐old adults). Scaling exponents and constants were assessed for standard (RS = 0·273M0·965 in mgO2 g−1 h−1) and active metabolic rate (RA = 0·799M0·926 in mgO2 g−1 h−1). These data provide the basis for further experiments regarding the effects of environmental factors on aerobic metabolism throughout the life cycle of this species.